Recent advances in cardiovascular surgery - Blalock, Alfred (1955)
Up to fifteen years the surgery of the heart and great vessels was limited to suturing wounds, drainage of infection of the pericardium, a pericardiectomy in constrictive pericarditis cases, the closure of arteriovenous fistulas, aneurysms loa wrapping wire and endoaneurysmorrhaphy. The field has broadened greatly in recent years and now are quite satisfactory procedures for the treatment of the following problems are known: (1) patent ductus arteriosus, (2) coarctation of the aorta, (3) tetralogy of Fallot, (4) pulmonary valve stenosis, (5) atrial septal defects, (6) septal defects, (7) mitral stenosis, (8) aortic stenosis (9) aortic insufficiency (10) of saccular aneurysms aorta, and (11) fusiform aneurysms of the aorta.